1991
DOI: 10.1002/tea.3660280907
|View full text |Cite
|
Sign up to set email alerts
|

Understanding models and their use in science: Conceptions of middle and high school students and experts

Abstract: Thirty‐three 7th‐grade mixed‐ability students and 22 11th‐grade honors students were interviewed about their conceptions of models and their use in science. Three analyses are presented in order to: (1) portray the character of students' spontaneous answers; (2) examine the criteria students use to decide whether specific items are models or not; and (3) describe how different general levels of understanding models reflect different epistemological viewpoints. Four experts were also interviewed for purposes of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
455
3
76

Year Published

1996
1996
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 555 publications
(557 citation statements)
references
References 7 publications
23
455
3
76
Order By: Relevance
“…Research on teacher knowledge in the domain of models and modeling has repeatedly indicated that teachers have very limited knowledge of the nature of models and the act of modeling (e.g., Justi & Gilbert, 2002, 2003Van Driel & Verloop, 1999). We assume that these shortcomings could be an important cause of the well-known problem in science education that many students consider a model to be a copy of the target (Grosslight, Unger, Jay, & Smith, 1991). To broaden textbook authors' and science teachers' conceptions of models and modeling, we think it is important to make them aware of the fact that models do not always explain empirical observations, and that not all models refer to a simplified representation of an abstract concept.…”
Section: Implications For Science Educationmentioning
confidence: 99%
“…Research on teacher knowledge in the domain of models and modeling has repeatedly indicated that teachers have very limited knowledge of the nature of models and the act of modeling (e.g., Justi & Gilbert, 2002, 2003Van Driel & Verloop, 1999). We assume that these shortcomings could be an important cause of the well-known problem in science education that many students consider a model to be a copy of the target (Grosslight, Unger, Jay, & Smith, 1991). To broaden textbook authors' and science teachers' conceptions of models and modeling, we think it is important to make them aware of the fact that models do not always explain empirical observations, and that not all models refer to a simplified representation of an abstract concept.…”
Section: Implications For Science Educationmentioning
confidence: 99%
“…When the literature was investigated, it was seen that there were studies to examine the opinions about model and modelling (Grosslight et al, 1991), the students' understanding about scientific models (Treagust et al, 2002), the preservice teachers' perceptions about role and purpose of models in science (Berber and Güzel, 2009), the teachers' opinions about models that is used in science (Güneş et al, 2004a), the science teachers' opinions about model and modelling (Ergin et al, 2012), the physics, chemistry, biology and science teaching staffs' opinions about models and role of models in science education (Güneş et al, 2004b). However, a study that was done in order to examine attitude towards using model wasn't seen.…”
Section: Sonuçmentioning
confidence: 99%
“…There was an underlying assumption that the process can be represented by many different models of different degree of sophistication. These are all characteristics of the expert view of modelling in the framework by Grosslight et al (1991) and in Justi and Gilbert's (2003) Also P2, the PhD student, gave an example of fitting the phenomenon to the model, when interpreting the constant pressure during intake and exhaustion. Only when giving the engine full gas, the model would be a reasonable representation:…”
Section: Relationship Between Model and Phenomenonmentioning
confidence: 99%
“…As a contrast, empirical studies have been made on ideas of modelling in science education. Grosslight et al (1991) performed an interview study on the conception of models and their use in science among students and experts.…”
Section: Introductionmentioning
confidence: 99%